Experimental Analysis of Auditor Performance Assessment Using A Reward System Which is Moderated by The Love of Money - Siregar, Wahyu Tri Putri; Irfan, Andi (Faculty of Economics and Business, Universitas Warmadewa, 2024)
Through the love of money as a moderating variable. Researchers seek to understand how rewards influence Performance. The sample used Bachelor of Accounting Audit students from UIN Suska Riau class of 2020. However, of the 73 people, only 42 passed the manipulation test and could be used in data processing. A 2 x 2 between-subjects design was used in this experimental research. The hypothesis in this study was tested using structured analysis of variance (ANOVA), and the experiment time lasted 25 minutes. The instruments used in this research were translation keys, cases, and questionnaires. The results show (1) that Performance will improve when auditors are promised rewards. (2) when an auditor with a high love of money attitude will improve Performance, and (3) when an auditor has a high love of money attitude and is promised a reward, the auditor will not improve Performance compared to an auditor with a low love of money attitude.